JOB INVOLVEMENT AS A MEDIATOR IN HOW HUMAN RESOURCE INFORMATION SYSTEMS DO AFFECT EMPLOYEE PERFORMANCE - Gilberto Rimang; Rosyid Nurrohman (JAMBURA: Jurnal Ilmiah Manajemen dan Bisnis, 2026)
The development of digitalization encourages companies to adopt Human Resource Information Systems (HRIS) as a strategic tool in managing human resources. This research aims to analyze the influence of the Human Resource Information System (HRIS) on employee performance with job involvement as a mediating variable. Research was conducted on employees of PT UTS Kaltim using a quantitative approach. Primary data was collected through questionnaires and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the help of the SmartPLS application. The research results show that HRIS has a positive and significant effect on employee performance and job involvement. Apart from that, job involvement has also been proven to have a positive and significant effect on employee performance. Furthermore, job involvement is able to positively and significantly mediate the influence of HRIS on employee performance. These findings indicate that effective HRIS implementation not only improves performance directly, but also through increasing employee work engagement. It is hoped that this research can provide a theoretical contribution in the development of HRIS and job involvement studies, as well as become practical consideration for companies in optimizing digital transformation in the field of human resources.